Proses Kolaborasi Pemerintah dan Masyarakat dalam Penanganan Kekerasan pada Anak di Kota Pekanbaru - Iqbal, Muhammad; Adianto, Adianto (Kolaborasi : Jurnal Administrasi Publik, 2026)
Violence against children remains a serious social issue in Pekanbaru City, as indicated by the fluctuating number of reported cases despite the implementation of child protection policies and the involvement of various institutions. This condition highlights the need for collaborative efforts among multiple actors, including government institutions and the community. This study aims to analyse the collaboration between the government and the community in handling violence against children in Pekanbaru City. This study employs a qualitative method with a phenomenological approach to understand the experiences and interactions of actors involved in child protection. Data were collected through semi-structured interviews and documentation involving DP3APM, the Social Service Office, the Police, and community actors through PATBM. Data analysis was conducted using NVivo 12 Plus to identify patterns and themes in the collaborative process. The results show that collaboration has been implemented through five components of collaborative governance: face to face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. This collaboration has contributed to improved responsiveness in case handling, better coordination in victim recovery services, and increased community participation in reporting cases. However, the collaboration still faces challenges, particularly the absence of integrated SOP or MoU across institutions and differences in operational coordination. Strengthening cross-sector coordination and developing integrated collaboration mechanisms are necessary to support a more effective and sustainable child protection system.